Analysis of radio propagation over rough sea surface with parabolic equation - GUO Jian-yan1; WANG Jian-ying2; LONG Yun-liang2 (Tongxin xuebao)
An improved impedance boundary method was presented and the initial field was calculated by Green function,which improved the stability and accurateness of the parabolic equation（PE）.Eventually,the forecast of propagation over rough sea surface had been presented with parabolic equation（PE）.The results from PE are compared with Miller-Brown model,good agreement is shown.